Subacute cutaneous lupus erythematosus presenting in twins. Issue 2 (13th February 2018) - Montuno, Michael A.; Church, Ann A.; Schoch, Jennifer J.; Andrews, Israel D.
Abstract: Subacute cutaneous lupus erythematosus is a clinically distinct form of cutaneous lupus erythematosus, with age of onset typically in the second to fifth decades. Eleven cases have been reported in childhood, and we present the first known case of subacute cutaneous lupus erythematosus in identical twins. Although flares are typically photo‐induced, we present an annular eruption typical of subacute cutaneous lupus erythematosus with concurrent pinworm infestation, with recurrence of disease with cutaneous larva migrans. The patient's identical twin had a similar eruption with pinworm infection. This case highlights the possibility of parasitic infestation as a trigger for subacute cutaneous lupus erythematosus in genetically susceptible individuals.